Perkembangan Psikososial Tokoh dalam Novel Twenty Karya Malichatus Sa'diyah: Kajian Psikologi Sosial Erikson dan Pemanfaatannya dalam Pembelajaran Sastra di SMA - Rr. Defi Arum Ramadhani (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to describe the psychosocial development of characters in the novel Twenty by Malichatus Sa’diyah based on Erik Erikson’s theory of psychosocial development, as well as its utilization as literary learning material for twelfth-grade senior high school students. This research employs a literary psychology approach, with data sources including the first edition of the novel Twenty published in 2021 by Elex Media Komputindo and the Merdeka Curriculum for Phase F (Grade XII). Data were collected through documentation techniques, involving careful reading and note-taking of relevant excerpts. The results show that the psychosocial development of the characters is dynamic. In the intimacy vs. isolation stage, the main character, Nala, experiences inner conflicts such as anxiety, jealousy, and fear of losing relationships, which indicate a tendency toward isolation; however, she eventually achieves emotional maturity, self-acceptance, and healthy interpersonal relationships. Meanwhile, in the generativity vs. stagnation stage, the character Mas Pandu demonstrates an orientation toward long-term commitment and social responsibility, despite differences in psychosocial readiness among characters. The implementation of this research is carried out by utilizing the findings as alternative teaching materials in senior high schools based on the Merdeka Curriculum to support active, contextual learning and to promote students’ critical, reflective, and appreciative thinking skills. Therefore, this study contributes both theoretically and practically to Indonesian language learning.
FINALISASI oleh Arif 2026 Juli 24
Keywords: Psychology of Literature; Erikson; Twenty Novel; Teaching Materials